Amended DV‐hop scheme based on N‐gram model and weighed LM algorithm. Issue 5 (1st March 2020) - Shi, Qinqin; Xu, Qiang; Zhang, Jianping
Abstract : Distance vector‐hop (DV‐hop) is a classical node localisation method for wireless sensor networks. Its main advantages are ease of use and excellent scalability, but its shortcomings are also very prominent for the high requirements on the network topology and low localisation accuracy in practical applications. An amended DV‐hop strategy is provided to improve the shortcomings of the classical DV‐hop including two aspects: one is that an N‐gram model is adopted to amend the distances between unknown nodes and beacons and the other is that a weighed Levenberg–Marquardt method is adopted to optimise the unknown nodes' initial positions. Simulation results show that compared with the original DV‐hop method and the other two typical improved methods, our proposed strategy improves the adaptability of the DV‐hop class methods to network topology changes, and the localisation accuracy is significantly enhanced.